A label-free electrochemical aptasensor based on AuNPs-loaded zeolitic imidazolate framework-8 for sensitive determination of aflatoxin B1. (1st August 2022) - Zhong, Tingting; Li, Shanshan; Li, Xin; JiYe, Yishang; Mo, Yuanyuan; Chen, Liying; Zhang, Zhiqing; Wu, Hejun; Li, Meiliang; Luo, Qingying
Highlights: An electrochemical aptasensor was developed for specific detection of aflatoxin B1. The presence of AuNPs/ZIF-8 on the sensor surface improved the loading of aptamers. The linear range of the aptasensor was wider than that of several reported sensors. The aptasensor was successfully used for the aflatoxin B1 detection in the edible oil. Abstract: In this study, an electrochemical aptasensor for sensitive detection of aflatoxin B1 (AFB1) was fabricated by electrodepositing gold nanoparticles (AuNPs) on the glass carbon electrode (GCE) modified with zeolitic imidazolate framework-8 (ZIF-8). The high specific surface area of AuNPs/ZIF-8 nanocomposite increased the aptamers loading on the electrode surface. When compared to other previously reported sensors, the developed aptasensor exhibited a wider linear range of 10.0 to 1.0 × 10 5 pg/mL with a lower limit of detection (LOD) of 1.82 pg/mL under the optimized conditions. Furthermore, the obtained results revealed that the constructed aptasensor exhibited outstanding selectivity, reproducibility and stability. Moreover, the aptasensor was successfully employed to detect the AFB1 in corn oil and peanut oil samples, with recoveries ranging from 93.49% to 106.9%, demonstrating the potential application value of this methodology.